2018
DOI: 10.1038/s41533-018-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and quality of life in adults and children during 3-years of SLIT treatment with Grazax—a real life study

Abstract: Respiratory allergic disease represents a global health problem, 30% of the population suffers from allergic rhinoconjunctivitis and 20% suffer from asthma. Allergy immunotherapy induce immunological tolerance and thereby modify the response to allergens and sublingual immunotherapy (SLIT) offers the possibility of home administration of allergen therapy, but adherence is more uncertain. The aim of the study was to investigate the adherence with GRAZAX in adults and children ≥ 5 years during three consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 36 publications
3
38
2
5
Order By: Relevance
“…In a short-term study on SCIT, 87.2% of patients were considered adherent (15), while in a 3-year study the adherence at the last year was 64.66% (18). In the two 3-years studies on adherence to SLIT, the same outcome was reported, 55% of patients completing the entire treatment (26,30). The only study comparing SCIT to SLIT reported a compliance rate of 58.7% in SCIT treated and 11.6% in SLIT treated patients (34).…”
Section: Other Issues Investigatedmentioning
confidence: 91%
See 1 more Smart Citation
“…In a short-term study on SCIT, 87.2% of patients were considered adherent (15), while in a 3-year study the adherence at the last year was 64.66% (18). In the two 3-years studies on adherence to SLIT, the same outcome was reported, 55% of patients completing the entire treatment (26,30). The only study comparing SCIT to SLIT reported a compliance rate of 58.7% in SCIT treated and 11.6% in SLIT treated patients (34).…”
Section: Other Issues Investigatedmentioning
confidence: 91%
“…The other topics were addressed in multiple studies. The most investigated was adherence and compliance, which was the subject of 5 studies (15,18,26,30). In a short-term study on SCIT, 87.2% of patients were considered adherent (15), while in a 3-year study the adherence at the last year was 64.66% (18).…”
Section: Other Issues Investigatedmentioning
confidence: 99%
“…♦ The first 3-12 months, when most nonpersistence occurs with both SLIT and SCIT, are crucial for patient education, patient engagement, and follow-up [43,45,48,61,62].…”
Section: Research Studies On Improving Ait Adherence: Key Findingsmentioning
confidence: 99%
“…♦ For SLIT local reactions, consider pretreatment with antihistamines, split tablet administration, moving tablet to other parts of vestibulum, and avoiding swallowing of the tablet [16,61].…”
Section: Research Studies On Improving Ait Adherence: Key Findingsmentioning
confidence: 99%
“…Wskaźnik adherence w przypadku AIT w opublikowanych analizach mieści się w granicach 40-70%. Są również takie prace, które wskazują, że wskaźnik ten sięga aż 90% [10,11,13]. Podobnie na wysoki odsetek adherence wskazały wyniki innego badania, real life, u chorych z alergią na jad owadów leczonych immunoterapią jadem (venom immunotherapy -VIT) przez 5 lat [14].…”
unclassified